Release properties of individual presynaptic boutons expressed during homosynaptic depression and heterosynaptic facilitation of the Aplysia sensorimotor synapse - Malkinson, Guy; Spira, Micha E. (Frontiers in Cellular Neuroscience, 2013)
Much of what we know about the mechanisms underlying Homosynaptic Depression (HSD) and heterosynaptic facilitation is based on intracellular recordings of integrated postsynaptic potentials. This methodological approach views the presynaptic apparatus as a single compartment rather than taking a more realistic representation reflecting the fact that it is made up of tens to hundreds of individual and independent Presynaptic Release Boutons (PRBs). Using cultured Aplysia sensorimotor synapses, we reexamined HSD and its dishabituation by imaging the release properties of individual PRBs. We find that the PRB population is heterogeneous and can be clustered into three groups: approximately 25% of the PRBs consistently release neurotransmitter throughout the entire habituation paradigm (35 stimuli, 0.05Hz) and have a relatively high quantal content, 36% of the PRBs display intermittent failures only after the tenth stimulation, and 39% are low quantal-content PRBs that exhibit intermittent release failures from the onset of the habituation paradigm. 5HT-induced synaptic dishabituation by a single 5HT application was generated by the enhanced recovery of the quantal content of the habituated PRBs and did not involve the recruitment of new release boutons. The characterization of the PRB population as heterogeneous in terms of its temporal pattern of release-probability and quantal content provides new insights into the mechanisms underlying HSD and its dishabituation.